Study of sensorineural hearing loss in children with type 1 diabetic mellitus and the corelation with the duration of the disease in a tertiary care center - Gowda, Mahesh; Pradeep, N (Indian Journal of Child Health, 2023)
Background: Annual type 1 diabetes cases in children under the age of 15 are estimated to be around 96,000 worldwide. The pathophysiological explanation for diabetes-related hearing loss is speculative. Usually, hearing loss is bilateral, gradual onset, affecting higher frequencies. It is a well-known entity in type 2 diabetic mellitus. This study aims at knowing the prevalence of hearing loss in children with type 1 diabetic mellitus with respect to duration of diabetic mellitus. Materials and Methods: A hospital-based comparative study was conducted involving 60 diabetic children and 60 healthy (control) children. Brainstem evoked response audiometry test was done in both groups. Reports were compared and prevalence of sensorineural hearing loss in diabetic children and the corelation with the duration of disease were analyzed. Results: The mean age among cases was 11.93±2.9 years and the mean age among controls was 9.08±1.92 years. Among diabetic group, 25 (41.7%) were male, 35 (58.3%) were female. Among non-diabetic group, 33 (55%) were male, 27 (45%) were female. Although none of the diabetic children had hearing loss, the differences in absolute latency waves I, II, III, IV, and V between diabetic group and non-diabetic group in the right ear and waves I and II and III and V between diabetic group and non-diabetic group in the left ear was found to be statistically significant (p